EKSISTENSI DAN FUNGSIONALITAS ADA DALAM BAHASA MELAYU MANADO (FUNCTIONALITY AND EXISTANCE OF ADA IN MANADO MALAY LANGUANGE) - Nurul Qomariah (Kadera Bahasa, 2016)
In Malay Manado there is duality functions held of ada form, both as verbs and particles. This research uses descriptive method. The population was the whole sentence containing forms exist in Malay Manado by purposive sampling technique. The method used is tapping the use of language in writing, followed by engineering log via the data, and then checking secondary data through consultation to the informan. The method used in this study, namely a unified method intralingual. This method analyzes the elements that are lingual in a language, in this case the elements in the form of Malay Manado. This study analyzed the theoretical approach of structural linguistics. This study foundthree things. First, the verb formation in Malay Manado through; affixation, reduplication, repetitive, reciprocal, and compounding. Second, the types of forms exist in Malay Manado through words and phrases. The form of words in the form polimorfemik formed through morphological process, namely through a form of affixation (prefixes, suffixes, konfiks) and reduplication (reduplicated perfect/intact, reduplication partial, reduplication resiprocal). The verb of Malay Manado form represented by affixing a repetitive phrase. Third, Malay Manado functionality through distribution forms of verbs and particles exist, to function as a predicate. Functional level verbs in this study occupied by the predicate. Level roles to fill in the verb predicate function there Malay Manado based on the results of this study are actions, processes, events, quantity, and circumstances.